From the edges to the center: Disability, Battlestar Galactica, and fan fiction. - Sasha_feather (Transformative Works & Cultures, 2010)
In this article, the author critically discusses how she succeeded in engaging disability concerns in both source text and fan responses in the case of Battlestar Galactica, also called BSG or Battlestar, which is an American military science fiction television series. The author says that she was excited about the show's promise of diversity for several reasons but particularly from the standpoint of disability. She further says that the fannish impulse to create stories and art, analyze media, and engage with other fans can lead to new opportunities and even new career paths for fans.